(3eLehYI QSGFds ((3WQGHdS s)
(3ChdgG (B:s
(3ZH EHdGZ JMjGJ UGajGJ, YfHQjI GdfaMGJ hJSdjeGJ hGajGJ, eScjI GdfSeGJ s
(3BNQgG (B:s
(3fNU Hg LfGH HGdeTGQ Edjg HGdCYdi, OGeJ CjGeg hdjGdjg HGdeSQGJ hGdJgGfj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B196 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs